Translocation of Proteins through a Distorted Lipid Bilayer - Wu, Xudong; Rapoport, Tom A. (Trends in cell biology, 2021)
Membranes surrounding cells or organelles represent barriers to proteins and other molecules. However, specific proteins can cross membranes by different translocation systems, the best studied being the Sec61/SecY channel. This channel forms a hydrophilic, hourglass-shaped membrane channel, with a lateral gate towards the surrounding lipid. However, recent studies show that an aqueous pore is not required in other cases of protein translocation. The Hrd1 complex, mediating the retrotranslocation of misfolded proteins from the endoplasmic reticulum (ER) lumen into the cytosol, contains multispanning proteins with aqueous luminal and cytosolic cavities, and lateral gates juxtaposed in a thinned membrane region. A locally thinned, distorted lipid bilayer also allows protein translocation in other systems, suggesting a new paradigm to overcome the membrane barrier. In all cells, proteins are translocated completely or partially across membranes. Translocases are generally required to overcome the energy barrier of a membrane.An entirely hydrophilic conduit is formed by the evolutionarily conserved SecY/Sec61 channel that is responsible for the secretion of proteins and the insertion of most membrane proteins.A growing number of translocase structures indicate that entirely hydrophilic channels are not always required. An example is the Hrd1 complex that mediates the retrotranslocation of misfolded proteins from the ER lumen into the cytosol. In this case, translocation occurs through luminal and cytosolic hydrophilic cavities and a locally thinned, distorted membrane region.In several other systems, translocation also occurs through a protein-induced distorted lipid bilayer, indicating a new paradigm for lowering the energy barrier.